2020
DOI: 10.1002/agg2.20012
|View full text |Cite
|
Sign up to set email alerts
|

Cover crop effects on soil carbon dioxide emissions in a semiarid cropping system

Abstract: Cover crops improve soil health and environmental quality by enhancing soil organic carbon (SOC) sequestration and nutrient cycling in agroecosystems. This study evaluated the effect of cover crops on soil CO2–C emissions, temperature, and water content during cover crop growth from April to October, 2017 and 2018. Treatments included fallow, pea (Pisum sativum L.), oat (Avena sativa L.), canola (Brassica napus L.), pea–oat (POmix), pea–canola (PCmix), pea–oat–canola (POCmix), and POC–hairy vetch (Vicia villos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Variation in results from different measurement systems may be related to their flux measurement mechanisms, chamber size, and soil environment. Our previous study in irrigated plots in the same study site show a significant effect of soil temperature and SMC in CO 2 emissions that low SMC, along with high soil temperature (>30 °C) can lower activity of microbial community involved in C and N cycling (Nilahyane, Ghimire, Thapa, & Sainju, 2020), consequently affecting GHG fluxes, irrespective management practices. The comparative study would help to understand the relative fluxes with various methods of CO 2 emissions monitoring.…”
Section: Discussionmentioning
confidence: 84%
“…Variation in results from different measurement systems may be related to their flux measurement mechanisms, chamber size, and soil environment. Our previous study in irrigated plots in the same study site show a significant effect of soil temperature and SMC in CO 2 emissions that low SMC, along with high soil temperature (>30 °C) can lower activity of microbial community involved in C and N cycling (Nilahyane, Ghimire, Thapa, & Sainju, 2020), consequently affecting GHG fluxes, irrespective management practices. The comparative study would help to understand the relative fluxes with various methods of CO 2 emissions monitoring.…”
Section: Discussionmentioning
confidence: 84%
“…Hence, more irrigation was provided in the second year than in the first year resulting in total irrigation + precipitation of 810-mm and 1040-mm in the first and second years, respectively. Studies demonstrated positive linear relationships between soil moisture, temperature, and substrate availability with CO 2 and N 2 O emissions 28 , 32 , 45 , 51 . In this study, correlation analysis showed that CO 2 -C emissions positively related to soil and air temperature (Supplementary Table S5 ).…”
Section: Discussionmentioning
confidence: 97%
“…Cover crops can enhance N cycling and increase C-sequestration due to increased biomass production and recycling 43 , 44 . This cover crop derived increase in C could increase CO 2 and N 2 O emissions in the first few years 32 , 45 . However, lower soil temperature under cover crops than under fallow could create a more conducive environment for C and N storage and cycling in the soils 45 , 46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A yield decline due to climate variability and water scarcity has also been documented in other areas of the world [15]. While cover crops use water for their growth, integrating cover crops in a crop rotation can reduce soil water loss by lowering daytime soil temperature and increasing ground cover [16][17][18]. Selection of low water use species with high ground cover potential minimizes soil water loss and increases crop yields in semi-arid regions where higher potential evapotranspiration restricts biomass production [7,19].…”
Section: Introductionmentioning
confidence: 99%